PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 028 SINTONG KECAMATAN TANAH PUTIH Ahmad - Rahmad Ripai Siregar; Eddy Noviana; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of this research is mathematics learning outcomes of students is low, with an average score of 55.8. Of the 25 students at Class IV of SD Negeri 028 Sintong Tanah Putih, students who completed as many as 9 peoples while not complete as many as 16 peoples. This research is a classroom action research (PTK) is done to improve learning outcomes Mathematics of students af class IV at SD Negeri 028 Sintong Tanah Putih by applying STAD type of cooperative learning model. The average score before action is 55.8 and after action on the first cycle increased to 70.8. In the UH II Cycle II increased to 80.6. The activities of teachers in the learning process at the first cycle in the first meeting is 54.2% and at the second meeting increase to 58.3%. At the first meeting of the second cycle of teacher activities increased to 79.2% and in the second meeting of the second cycle increased to 95.8%. Similarly, analysis of the activities of the students at the first meeting of the first cycle was 45.8% and increased in the second meeting of the first cycle to 58.3%. At the first meeting of the second cycle of student activities is 79.2% and in the second meeting of the second cycle increased to 91.7%. This Research results in the fourth grade SD Negeri 028 Sintong Tanah Putih prove that the implementation of cooperative learning model STAD Type can improve learning outcomes Mathematics at Class IV SD Negeri 028 Sintong Kecamatan Tanah Putih.Keywords: STAD, mathematic learning outcomes